Ivabradine therapy and correction of the target organ pathology in patients with ischemic chronic heart failure - M. V. Surovtseva; N. A. Koziolova; A. I. Chernyavina (Российский кардиологический журнал)
Aim. To assess the therapeutic potential of ivabradine, as a part of complex treatment regime, for the correction of the target organ pathology in patients with chronic heart failure (CHF) of ischemic aetiology. Material and methods. In total, 90 patients with Functional Class II–III CHF and stable angina were examined. All participants were divided into three groups, by the type of 6-month antiischemic therapy: Group 1 received perindopril and ivabradine; Group 2 was administered perindopril, bisoprolol, and ivabradine; and Group 3 received perindopril and bisoprolol. At baseline and after 6 months of the treatment, the following renal and arterial parameters were assessed: glomerular filtration rate (GFR; MDRD formula); pulse wave velocity (PWV measured for elastic-type vessels on the right and left side: R-PVW and L-PVW); cardiac-ankle-vascular index (CAVI1); carotid-femoral PWV (PWVcf); aortic PWV (PWV) and carotid PWV (C-PWV); and radial and carotid augmentation index (R-AI and C-AI). In addition, blood levels of the following biomarkers were measured: N-terminal pro B-type natriuretic peptide (NT-proBNP); and key markers of renal and arterial extracellular collagen matrix: tissue inhibitor of matrix metalloproteinase 1 (TIMP-1) and C-terminal telopeptide of collagen 1 (CTP-1). Results. After 6 months of a complex ivabradine-including therapy, a significant positive dynamics was observed for the levels of GFR, TIMP-1 and CTP-1 (extracellural collagen matrix markers), and NT-proBNP (a myocardial stress marker). The improvement in arterial wall structure and function was manifested in both reduced stiffness (decreased CAVI1 and PWVcf) and increased elasticity and distensibility (decreased PWV and C-PWV). The improvement in arterial elasticity and distensibility was significantly greater in patients receiving the three-medication therapy. Conclusion. The findings on the ivabradine therapy, as a part of complex treatment regime in patients with ischemic CHF, demonstrated nephro- and vasoprotective effects of ivabradine.